Hypomagnesaemia in Pregnancy: A predictor of Preterm Labour (Journal of Dhaka Medical College, 2010)
Preterm birth is a major health concern. It is the leading cause of perinatal mortality and morbidity. Besides varied etiology, it may be due to alteration in basic biochemical function of the body at cellular level stating emphasis to trace elements of which magnesium, being one of them. Pregnancy is marked by a state of hypomagnesaemia and varied hypomagnesaemia is observed in preterm labour cases. The study is conducted to find out the relationship between low serum magnesium concentrations with preterm labour, with a view to ascertain it as one of the predictor of preterm labour. This study has been designed as cross sectional case control study. 100 pregnant women with preterm labour were taken as case and 100 women with term labour as control. It is found that mean level of serum magnesium was lower in preterm labour as compared with term labour. The study shows that there is significant decrease in magnesium in maternal body in case of preterm labour. The study also shows that the relative risk of preterm labour was 3.18 times more in patients with serum magnesium level less than 1.9 mg/ dl in comparison to those who had the level of 1.9 mg/dl or more. Low level of serum magnesium significantly correlated with the preterm labour. Moreover different studies also shows that the decreased serum magnesium level has an association with the uterine irritability leads to the preterm labour. As such, it is assumed that the low serum magnesium concentration in pregnancy has a role in pathophysiology of preterm labour and may be used as a predictor of preterm labour. Key words: Hypomagnesaemia; predictor; preterm labour. DOI: 10.3329/jdmc.v19i1.6253 J Dhaka Med Coll. 2010; 19(1) : 51-57